Multimodality In “Bakiak Games” Posts on G20 2022 Social Media - Ahmadi F, Yusep; Syaifullah, Aceng Ruhendi; Hermawan, Budi (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2024)
This study aims to reveal the meaning of the message in the multimodal post "Bakiak Game" on Instagram G20 2022. This is to see how the Bakiak Game is depicted and what reflects its ideology. The focus of this research is on describing the ideational meaning of verbal and visual data. This research method is qualitative with a multimodal discourse analysis approach. The data source for this research is multimodal posts in the form of a combination of visual mode (image) and verbal mode (caption). The post in question is a post about "The Game of Bakiak" which was uploaded on social media Instagram G20 2022. Based on the analysis of the verbal mode, material processes, relational processes and behavioral processes were found in describing the game of Bakiak. Of these three processes, the material process is very dominant. This shows that Bakiak is described as a physical sport carried out by humans in groups. Apart from that, in the image mode, an actional narrative process is found. This is in line with the ideational meaning in the verbal mode, namely that this post describes a physical sport carried out in a group and coordinated. Ideologically, this game has the moral value of cooperation and team coordination. In the context of the spirit and moral values ​​of the G20, it needs to be adopted by the global community, especially the G20 countries, in facing the challenges after the Covid-19 pandemic.